Cleomin Exerts Acute Antinociceptive Effects in Mice via GABAB and Muscarinic Receptors - Luíza Carolina França Opretzka; Max Denisson Maurício Viana; Alyne Almeida de Lima; Thalisson Amorim de Souza; Marcus Tullius Scotti; Josean Fechine Tavares; Marcelo Sobral da Silva; Milena Botelho Pereira Soares; Cristiane Flora Villarreal (MDPI AG, 2023)
Cleomin, a 1,3-oxazolidine-2-thione, was recently isolated from Neocalyptrocalyx longifolium, a species traditionally used for treating painful conditions. Reports about the pharmacological activities of cleomin are lacking. Here, the antinociceptive effects of cleomin were investigated using mice models of pain, namely the formalin, the cold plate, and the tail flick tests. Motor integrity was assessed in the rota-rod test. Antagonism assays and in silico docking analyses were performed to investigate the putative mechanisms of action. Cleomin (12.5-25 mg/kg), at doses that did not induce motor impairment, induced dose-dependent antinociception in both early and late phases of the formalin test and reduced nociceptive behaviors in both the cold plate and tail flick tests. Pretreatments with phaclofen and atropine attenuated the antinociceptive effects of cleomin, implicating the involvement of GABAB and muscarinic receptors. In silico docking studies suggested satisfactory coupling between cleomin and GABAB and M2 receptors, hence corroborating their role in cleomin's activity. Pretreatments with naloxone, yohimbine, bicuculline, and methysergide did not affect the antinociception of cleomin. In silico pharmacokinetics prediction showed a good drug ability profile of cleomin. In conclusion, cleomin promoted antinociception mediated by GABAB and muscarinic receptors. These findings support further investigation of the analgesic potential of cleomin.